Managing uncertainty in design flood magnitude: Flexible protection strategies versus safety factors. Issue 2 (20th May 2018) - Dittes, B.; Špačková, O.; Straub, D.
Abstract : When planning flood protection, agencies are confronted with uncertainty in the design flood magnitude. In particular, the required capacity may increase in the future and render the protection insufficient. This problem can be adressed by applying a safety factor to the design capacity. We propose a Bayesian quantitative sequential decision model that identifies a cost‐optimal safety factor in the face of uncertainty. It takes into account the flexibility of the protection system, that is, how costly it is to adjust. We focus on the description of the decision model and on the concept of flexibility, investigating only the effect of uncertainty from the historic flood record. Extension to other types of uncertainty is possible. The model is implemented for a catchment in Germany. Various degrees of uncertainty are investigated by using different lengths of historic records. The optimal safety factor decreases with decreasing uncertainty and with increasing system flexibility.